Roles of central nervous system resident and recruited macrophages in the brain barrier system - Ze Liu; Teng Cheng; Hongtian Dong; Dingya Sun; Yan Wang; Jiayan Li; Zhongwang Yu; Li Cao (Neural Regeneration Research)
Macrophages in the brain barrier system include microglia in the brain parenchyma, border-associated macrophages at the brain’s borders, and recruited macrophages. They are responsible for neural development, maintenance of homeostasis, and orchestrating immune responses. With the rapid exploitation and development of new technologies, there is a deeper understanding of macrophages in the brain barrier system. Here we review the origin, development, important molecules, and functions of macrophages, mainly focusing on microglia and border-associated macrophages. We also highlight some advances in single-cell sequencing and significant cell markers. We anticipate that more advanced methods will emerge to study resident and recruited macrophages in the future, opening new horizons for neuroimmunology and related peripheral immune fields.